Conducting the Pakistan brain tumour epidemiology study - report on the methodology - Erum Baig ,; Mashal Murad Shah ,; Mohammad Hamza Bajwa,; Muhammad Usman Khalid ,; Saad Akhtar Khan ,; Ummey Hani ,; Saad bin Anis ,; Altaf Ali Laghari,; Naveed Zaman Akhunzada ,; Jaleed Ahmed Gilani,; Noyan Jawed,; Muhammad Faraz Raghib ,; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To combat the lack of brain tumour registries, the Pakistan Brain Tumour Epidemiology Study (PBTES) was conducted without any funding from an external source. Methods: A retrospective analysis of patient data, including patients of all age groups diagnosed with all histopathological types of brain tumours from all over Pakistan, was performed. For this, Pakistan Brain Tumour Consortium (PBTC) was established, including 32 neurosurgical centres from around the country. Data was collected online through a proforma that included variables such as patient demographics, clinical characteristics, operative details, postoperative complications, survival indices, and current functional status. The data collection and analysis team included principal investigators, core leads, regional leads, regional associates, and student facilitators. Despite logistical concerns and lack of resources, the PBTES was conducted successfully, and a formal brain tumour surveillance database was formed without any external funding, which remains unheard of. Conclusion: The methods applied in this study are reproducible and can be employed not just to develop more robust brain tumour and other cancer registries but also to study the epidemiology of communicable and non-communicable diseases in resource-limited settings, both locally and globally. Keywords: brain neoplasms, retrospective study, epidemiology, noncommunicable diseases. Continue...